Assessing environmental conditions of Antarctic footpaths to support management decisions. (15th July 2016) - Tejedo, Pablo; Benayas, Javier; Cajiao, Daniela; Albertos, Belén; Lara, Francisco; Pertierra, Luis R.; Andrés-Abellán, Manuela; Wic, Consuelo; Luciáñez, Maria José; Enríquez, Natalia; Justel, Ana; Reck, Günther K.
Abstract: Thousands of tourists visit certain Antarctic sites each year, generating a wide variety of environmental impacts. Scientific knowledge of human activities and their impacts can help in the effective design of management measures and impact mitigation. We present a case study from Barrientos Island in which a management measure was originally put in place with the goal of minimizing environmental impacts but resulted in new undesired impacts. Two alternative footpaths used by tourist groups were compared. Both affected extensive moss carpets that cover the middle part of the island and that are very vulnerable to trampling. The first path has been used by tourists and scientists since over a decade and is a marked route that is clearly visible. The second one was created more recently. Several physical and biological indicators were measured in order to assess the environmental conditions for both paths. Some physical variables related to human impact were lower for the first path (e.g. soil penetration resistance and secondary treads), while other biochemical and microbiological variables were higher for the second path (e.g. β-glucosidase and phosphatase activities, soil respiration). Moss communities located along the new path were also more diverse and sensitive to trampling. Soil biota (Collembola) was also more abundant and richer. These data indicate that the decision to adopt the second path did not lead to the reduction of environmental impacts as this path runs over a more vulnerable area with more outstanding biological features (e.g. microbiota activity, flora and soil fauna diversity). In addition, the adoption of a new route effectively doubles the human footprint on the island. We propose using only the original path that is less vulnerable to the impacts of trampling. Finally from this process, we identify several key issues that may be taken into account when carrying out impact assessment and environmental management decision-making in the Antarctic area. Highlights: The adoption of a new footpath resulted in additional environmental impacts. Results from a global assessment led to our proposal to close the new path. Impact assessment should extend beyond initial visual inspection. If possible, management decisions should be based on solid scientific knowledge. First record of an invasive non-indigenous Collembola species on Barrientos Island.